Commutators of Littlewood-Paley Operators on Herz Spaces with Variable Exponent (Analysis in Theory and Applications, 2016)
Let $Ω\in L^2(S^{n-1})$ be homogeneous function of degree zero and $b$ be BMO functions. In this paper, we obtain some boundedness of the Littlewood-Paley Operators and their higher-order commutators on Herz spaces with variable exponent.
Keywords: Herz space; variable exponent; commutator; area integral; Littlewood-Paley $g_λ^*$ function.